Peer and parental correlates of driving anger and its expression - Adams, Megan M., author; Deffenbacher, Jerry L., advisor; Vacha-Haase, Tammi, committee member; Clegg, Benjamin, committee member; MacPhee, David, committee member (Colorado State University. Libraries, 2006)
A large body of literature has shown that parents and peers serve as models and reinforcers of an individual's general anger and aggression. A small but growing body of literature has indicated that peers and parents likewise influence driving behaviors through modeling, reinforcement, and monitoring. This study added to understanding the development of driving anger and aggression by exploring the relationship of driving-related emotions, emotional expression, and behaviors to perceived influence of parents and peers. Participants were 329 undergraduate students (M age = 18.8) who completed the Driving Anger Scale (Deffenbacher et al., 1994), the Driving Anger Expression Inventory (Deffenbacher et al., 2002), Driving Survey (Deffenbacher, Deffenbacher, et al., 2003), Trait Anger Scale (Spielberger, 1988), Anger Expression Inventory (Spielberger, 1988), and Scales of Peer and Parental Influence, developed for this study. Reliable measures of peer (modeling, encouragement, and discouragement) and parent influence (modeling, encouragement, discouragement, and monitoring) were developed (αs = .85 to .99). Gender contributed a significant amount of variance to the prediction of adaptive/constructive anger expression, aggressive expression, aggressive and risky behavior but did not contribute to prediction of driving anger. Women reported more use of positive, constructive anger expression, whereas men reported more aggressive expression, aggression, and risky behaviors. Modeling and encouragement by peers and parents predicted driving anger, aggression, and risky behaviors. Discouragement was largely unrelated or actually positively related. The inclusion of an individual's general anger and anger expression in the models reduced the contributions of peer and parental influence variables. However, once variance was accounted for by the general anger measures, at least one influence variable contributed to prediction of driving anger and anger expression. Parental monitoring was the most consistent factor in the prediction of participants' driving anger and anger expression while modeling and encouragement by parents and peers also contributed. Findings replicated past studies on gender differences on driving anger expression and parental monitoring of roadway behavior. Findings strengthened the literature on the influence of parents and peers as models for the development of anger, aggression, and/or risky behaviors. Results have potential value for prevention efforts utilizing peer and parent education programs.
Keywords: social psychology; developmental psychology